Use of Nonantiretroviral Medications That May Impact Neurocognition: Patterns and Predictors in a Large, Long-Term HIV Cohort Study. (1st June 2018) - Radtke, Kendra K.; Bacchetti, Peter; Anastos, Kathryn; Merenstein, Daniel; Crystal, Howard; Karim, Roksana; Weber, Kathleen M.; Edmonds, Andrew; Sheth, Anandi N.; Fischl, Margaret A.; Vance, David; Greenblatt, Ruth M.; et al.
Abstract : Background: Neurocognitive impairment is a frequent and often disabling comorbidity of HIV infection. In addition to antiretroviral therapies, individuals with HIV infection may commonly use nonantiretroviral medications that are known to cause neurocognitive adverse effects (NC-AE). The contribution of NC-AE to neurocognitive impairment is rarely considered in the context of HIV and could explain part of the variability in neurocognitive performance among individuals with HIV. Setting: Women's Interagency HIV Study, a prospective, multisite, observational study of US women with and without HIV. Methods: After a literature review, 79 medications (excluding statins) with NC-AE were identified and reported by Women's Interagency HIV Study participants. We examined factors associated with self-reported use of these medications over a 10-year period. Generalized estimating equations for binary outcomes were used to assess sociodemographic, behavioral, and clinical characteristics associated with NC-AE medication use. Results: Three thousand three hundred women (71% with HIV) and data from ∼42, 000 visits were studied. HIV infection was associated with NC-AE medication use (odds ratio = 1.52; 95% confidence interval: 1.35 to 1.71). After adjustment for HIV infection status, other predictors of NC-AE medication use included having health insurance, elevated depressive symptoms, prior clinical AIDS, noninjection recreational drug use, and an annual household income of <$12, 000 ( P s < 0.004). NC-AE medication use was less likely among women who drank 1–7 or 8–12 alcoholic drinks/week (vs. abstaining) ( P < 0.04). Conclusions: HIV infection was associated with NC-AE medication use, which may influence determinations of HIV-associated neurocognitive impairment. Providers should consider the impact of NC-AE medications when evaluating patients with HIV and concurrent neurocognitive symptoms. Abstract : Supplemental Digital Content is Available in the Text.